2015
DOI: 10.4067/s0717-75182015000100010
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de edulcorantes no calóricos en la calidad sensorial de jugo de naranja

Abstract: INTRODUCCIÓN El sabor dulce juega un rol muy importante en los seres humanos, ya que la mayoría de las personas responden positivamente a la sensación de dulzor, y existe una propensión al consumo de alimentos dulces que se remonta a la vida temprana (1). Los edulcorantes utilizados en la industria alimentaria se dividen en 2 grandes grupos: calóricos y no calóricos. Entre los edulcorantes no calóricos de mayor consumo se encuentran la sacarina de sodio cuyo poder edulcorante es 200 a 700 superior al azúcar, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(24 reference statements)
0
1
1
3
Order By: Relevance
“…The statistical analysis showed that there was a significant difference among treatments (p-value 0.001), as a consequence, the aroma attribute was influenced by the different treatments, according to the panelists' evaluation. By coincidence, the clarified beverages belonging to treatments (T 3 and T 5 ) and the non-clarified ones belonging to treatments (T 4 and T 6 ), which had stevia addition, had a higher evaluation by the panelists, approaching a "medium" on a scale ranging from "no aroma" to "extremely aromatic", which is not in line with the results obtained by (Quitral et al, 2015), who pointed out that the aroma of juices is not affected by the type of sweetener. In regards to the values of the aroma attribute perceived by the panelists, they were similar for clarified and non-clarified beverages, although there was a slight tendency or a higher selection of the aroma attribute for the clarified beverages elaborated in treatment (T 5 ), but they were not significant.…”
Section: Aromacontrasting
confidence: 66%
“…The statistical analysis showed that there was a significant difference among treatments (p-value 0.001), as a consequence, the aroma attribute was influenced by the different treatments, according to the panelists' evaluation. By coincidence, the clarified beverages belonging to treatments (T 3 and T 5 ) and the non-clarified ones belonging to treatments (T 4 and T 6 ), which had stevia addition, had a higher evaluation by the panelists, approaching a "medium" on a scale ranging from "no aroma" to "extremely aromatic", which is not in line with the results obtained by (Quitral et al, 2015), who pointed out that the aroma of juices is not affected by the type of sweetener. In regards to the values of the aroma attribute perceived by the panelists, they were similar for clarified and non-clarified beverages, although there was a slight tendency or a higher selection of the aroma attribute for the clarified beverages elaborated in treatment (T 5 ), but they were not significant.…”
Section: Aromacontrasting
confidence: 66%
“…So far, we do not know how consumer preferences in terms of sweetness and flavors could lead to this reformulation. However, insights from a study focused on the sensory evaluation of orange juice sweetened with sugars or different NNS types showed that the juices sweetened with sugars or sucralose had greater acceptability than juices sweetened with other NNS in a small sample of college students ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…| Para la evaluación sensorial, se utilizó una prueba de aceptabilidad conocida como nivel de agrado (Ramírez-Navas, 2012) que consiste en determinar si existen diferencias entre las muestras que se evalúan a través de escalas hedónicas de 3, 5, 7 y 9 puntos. Para el ejercicio, se empleó una escala hedónica de 5 puntos, un modelo aplicado en estudios por Quitral ( 2015), donde se evalúan atributos como olor, sabor y textura (Ramírez-Navas, 2012). La tabla 2 muestra el grado de evaluación que se empleó durante el estudio con una escala de 5 puntos.…”
Section: Cuadrounclassified